Effect of Customer Satisfaction On the Profitability of Fast Food Outlets in Akwa Metropolis of Anambra State - Chendo; Augustina, Nkoli (British Journal of Marketing Studies, 2023)
The study examined the effects of customer satisfaction on the profitability of fast food industry in Akwa Metropolis of Anambra State. The specific objective is to determine the extent to which customer service affects the profitability of fast food industry in Awka metropolis. To evaluate the extent to which customer experience affects the profitability of fast food industry in Awka metropolis. To examine the extent to which product quality affects the profitability of fast food industry in Awka metropolis. The research utilized a survey research design method, a structured instrument developed by the researcher to reflect such options as strongly agree, agree, undecided, disagree and strongly disagree popularly refereed as five (5) points Likert scale was used to obtain information from the respondents. The population of the study comprised of 324 employee of fast food in Akwa metropolis.297 copies of questionnaires was duly completed and returned showing 96% response rate. Research hypotheses were tested using Chi-square. Findings from the study show that Customer service has significant effect on profitability of fast food industry in Awka metropolis. Customers experience has significant effect on profitability of fast food industry in Awka metropolis. Product quality has no significant effect on profitability of fast food industry in Awka metropolis. Maintaining existing customers should be a better option than chasing for new because a customer who is satisfied will have a positive dissonance about the service and who always recommend the service to friends and family who are potential customers. Further research should be carried out in order to enhance the understanding of the concepts of service quality and customer satisfaction, how they are measured because they are very important for service organizations in terms of profitability, growth and market share. Citation: Chendo, N.A. (2023) Effect of Customer Satisfaction On the Profitability of Fast Food Outlets in Akwa Metropolis of Anambra State, British Journal of Marketing Studies, Vol. 11, Issue 1, pp.,12-25